Knockdown of amyloid precursor protein in zebrafish causes defects in motor axon outgrowth. - Ping Song; Sanjay W Pimplikar (PLoS ONE)
Amyloid precursor protein (APP) plays a pivotal role in Alzheimer's disease (AD) pathogenesis, but its normal physiological functions are less clear. Combined deletion of the APP and APP-like protein 2 (APLP2) genes in mice results in post-natal lethality, suggesting that APP performs an essential, if redundant, function during embryogenesis. We previously showed that injection of antisense morpholino to reduce APP levels in zebrafish embryos caused convergent-extension defects. Here we report that a reduction in APP levels causes defective axonal outgrowth of facial branchiomotor and spinal motor neurons, which involves disorganized axonal cytoskeletal elements. The defective outgrowth is caused in a cell-autonomous manner and both extracellular and intracellular domains of human APP are required to rescue the defective phenotype. Interestingly, wild-type human APP rescues the defective phenotype but APPswe mutation, which causes familial AD, does not. Our results show that the zebrafish model provides a powerful system to delineate APP functions in vivo and to study the biological effects of APP mutations.